The digital Silk Road and China's influence on standard setting - Alex He (Centre for International Governance Innovation (CIGI), 2022)
China is striving to become a leader in international standard setting, and the Digital Silk Road, part of China's Belt and Road Initiative to expand its global infrastructure and markets, is key to realizing this goal. Both roads depend on standard connectivity, fuelled by Chinese private companies that are the driving force behind China's growing role as a leader in technology development and shaping standards in both domestic and global markets. However, China faces strong competition to gain more influence in international standard-setting bodies, which are dominated by the European Union and the United States.
Keywords: 330